Using Graph Theory to Assess the Interaction between Cerebral Function, Brain Hemodynamics, and Systemic Variables in Premature Infants. (9th August 2018) - Hendrikx, Dries; Thewissen, Liesbeth; Smits, Anne; Naulaers, Gunnar; Allegaert, Karel; Van Huffel, Sabine; Caicedo, Alexander
Abstract : Graphs can be used to describe a great variety of real-world situations and have therefore been used extensively in different fields. In the present analysis, we use graphs to study the interaction between cerebral function, brain hemodynamics, and systemic variables in premature neonates. We used data from a propofol dose-finding and pharmacodynamics study as a model in order to evaluate the performance of the graph measures to monitor signal interactions. Concomitant measurements of heart rate, mean arterial blood pressure, arterial oxygen saturation, regional cerebral oxygen saturation—measured by means of near-infrared spectroscopy—and electroencephalography were performed in 22 neonates undergoing INSURE (intubation, surfactant administration, and extubation). The graphs used to study the interaction between these signal modalities were constructed using the RBF kernel. Results indicate that propofol induces a decrease in the signal interaction up to 90 minutes after propofol administration, which is consistent with clinical observations published previously. The clinical recovery phase is mainly determined by the EEG dynamics, which were observed to recover much slower compared to the other modalities. In addition, we found a more pronounced loss in cerebral-systemic interactions with increasing propofol dose.